2014
DOI: 10.1021/jo501197y
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Substituted Tetrahydrofurans via Prins Cyclization of Enol Ethers

Abstract: Indium triflate can be efficiently used for Prins cyclization of acrylyl enol ethers to give tetrahydrofuran ring stereo- and regioselectively in good yields. The formation of five-membered rings is against the Baldwin's rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…2). [31] A substoichiometric amount of In(OTf) 3 was used to promote the unusual 5-endo-trig cyclisation of 20, which proceeded under formation of the ketone 21 from hydrolysis of the carbocation after cyclisation.…”
Section: B) Cyclisations Of Enol Ethers With Olefins and Allenesmentioning
confidence: 99%
“…2). [31] A substoichiometric amount of In(OTf) 3 was used to promote the unusual 5-endo-trig cyclisation of 20, which proceeded under formation of the ketone 21 from hydrolysis of the carbocation after cyclisation.…”
Section: B) Cyclisations Of Enol Ethers With Olefins and Allenesmentioning
confidence: 99%
“… Here, we report that indene derivatives could also be prepared from homopropargyl alcohols, aldehydes and arenes, promoted by boron trifluoride diethyl etherate at room temperature (eq 2). The reactions between homopropargyl alcohols and aldehydes are known to form furans (eq 3) via Lewis acid catalyzed Prins cyclizations. , In the presence of aromatic solvents and boron trifluoride diethyl etherate, we found that the cascade reaction was further extended to yield indenes. …”
mentioning
confidence: 93%
“…2 Prins reactions have also been used to obtain derivatives of tetrahydrofuran and other rings up to macrocycles. 1a,d, 3 Prins reactions of aza-and thiocyclization leading to pipyridines and tetrahydrothiopyranes are not so widespread. 4, 5 Using a Prins carbocation intermediate in tandem transformations has led to new approaches to natural compounds: Overman's Prins-pinacol cascade, 6 tandem aza-Prins-Ritter/ Friedel-Crafts sequences, 7 Prins-ene reactions, 8 Prins-2-oxoniaCope rearrangements 1d,9 etc., were developed.…”
Section: Introductionmentioning
confidence: 99%